Isolation, Characterization and Application of DNA Microsatellite Markers in Mungbean (Vigna Radiata L. Wilczek) and Other Selected Legumes - Vijay Kumar, (2003)
Mungbean (subgenus Ceratotropis) is an important food source in many parts of the world, particularly in Asia and Southeast Asia. It is an important source of plant protein and calcium, and is a good substitute for meat. Although it is an important crop, little is known about its genetic background. DNA markers, in particular micro satellites, are able to provide insights regarding the genetic structure and background of populations and thus would be of great benefit in mungbean improvement programs. Three techniques were used to isolate micro satellite loci in mungbean, namely direct amplification of length polymorphism (DALP), 5' anchored PCR and random hybridizing micro satellites (RAHM). A total of 107 repeat sequences were identified of which 80% were micro satellite loci and 20% were cryptic simple regions. The majority of micro satellites were found using the 5' anchored PCR procedure which proved to be the most efficient technique in the present study, while DALP did not produce any microsatellite.